Multi-player android game using near field communication / Che Nur Afiqah Che Hashim - Che Hashim, Che Nur Afiqah (2015)
Mobile application recently showed tremendous growth in demand and its development especially in mobile game. Mobile game can lead to negative effects in social life. Children are easily addicted to them and adults are having problem with real life socializing if interactions with the screen is more interesting than interactions with another person. Near Field Communication (NFC) is of the current technology which allows communication between devices in a short distance. The awareness of NFC is not the same level with Bluetooth and Infrared. Motivated by these circumstances, a mobile game application is developed to solve socializing issues, promote the use of NFC and create educational game application suitable for all ages. Instead of playing multiple players virtually, the game applied NFC as communication between devices and creates a multi-player game environment in real life. To complete the project, a research methodology framework is designed. Starting from preliminary study, the progress continued to designing phase, development phase until testing and implementation phase. A documentation of the project is done at the final phase. Evaluation of the project is made by conducting a survey on user interfaces, project usability and application functionality. The feedback is recorded for future works for the enhancement of the project. This project can bring a new approach of implementing NFC in multi-player mobile game and diversify the use of NFC in other types of application as well.